Globalization, de-globalization, and re-globalization: Some historical context and the impact of the COVID pandemic. Issue 3 (July 2021) - Madhok, Anoop
The Covid-19 pandemic has exposed many of the weaknesses in our current systems of government and commerce. In this essay, I provide some historical context to the recent era of "hyper-globalization." I then present multiple factors—economic, social, political, technological, and governance-related—that collectively explain why globalization has peaked and is on the retreat. Following this, I use the analogy of a three-legged stool to explain the importance of recalibrating the economy, state, and society so as to realize a healthier alignment among them. Finally, I look at where globalization might be going next and the implications for firms, concluding with some lessons that we can take away from the COVID crisis. JEL CLASSIFICATION: M10, M16, M19